Application of epicutaneo-cava catheters with 24G indwelling needles in very low birth weight infants: a safe and simple innovative technique - Wang, Qin; Luo, Feixiang; Fan, Xiaoyan; Cheng, Xiaoying; Ma, Xiaolu; Shi, Liping; Zhang, Pei (Frontiers in Pediatrics, 2023)
Background Epicutaneo-cava catheter (ECC) is an ideal venous access for very low birth weight (VLBW) infants. However, because veins of VLBW infants are thin, ECC catheter is difficult to insert, and the success rate of puncture is low. This study aimed to use ECC with 24G indwelling needles to improve the outcomes of VLBW infants. Methods This retrospective study enrolled 121 VLBW infants (birthweight <1,500 g) who required ECC catheterization and were admitted to the Neonatal Intensive Care Unit of the Children's Hospital of Zhejiang University School of Medicine between January 2021 and December 2021. The patients were divided into the indwelling needle group and the conventional technique group according to the technique of ECC. The demographic and treatment data of the two groups were collected, and the success rate of first attempt cannulation of ECC and catheter-related complications of the two groups were analyzed and compared. Results There were no significant differences in gender, age, and body weight between the two groups on the day of ECC insertion and venipuncture site. It can be seen through model analysis that the success rate of first-attempt cannulation of ECC in the indwelling needle group was significantly higher than in the conventional technique group. In contrast, average catheterization time and catheterization-related bleeding risk in the indwelling needle group were significantly lower than in the conventional technique group (p = 0.00,and 0.00, respectively). Infection during catheter placement, indwelling catheter duration and catheter-related infection between the two groups (p > 0.05). Conclusion Application of ECC with 24G indwelling needles in VLBW infants can improve the success rate of first attempt cannulation of ECC, reduce the time of catheterization and the risk of bleeding, which may be popularized for widespread application.